Effect of carbonization temperature on properties of natural fiber and charcoal filled hybrid polymer composite. (15th July 2021) - Kumar, Ritesh; Gunjal, Jayashri; Chauhan, Shakti
Abstract: In this study, bamboo fiber filled polypropylene composites (BPCs) were prepared using bamboo and coconut shell charcoal as reinforcing fillers for enhancing the properties of composites. Bamboo and coconut shell biomass were carbonized at different carbonization temperatures (300, 400, 600, and 900 O C); 1 h soaking time and at 5 O C −min heating rates. The effect of carbonization temperature and charcoal content (0.5%, 1.0% and 1.5%) on mechanical, thermal and water absorption properties of BPCs has been investigated. The experimental results show that charcoal which is obtained at lower pyrolysis temperature (300 O C and 400 O C) improves the strength properties of BPCs, whereas, strength properties remains unaltered when charcoal prepared at elevated temperatures (600 O C and 900 O C) are added to BPCs. Compared to coconut shell charcoal (CSC) better mechanical properties were obtained through bamboo charcoal (BC). This has been attributed to flakes like appearance of BC, having pores present on their surfaces. The study also shows that addition of charcoal provides thermal stability to BPCs, particularly via charcoal prepared at elevated temperature (900 O C). The optimum temperature for achieving sufficient hydrophobicity in BPCs is found to be 300 O C and 600 O C for BC and CSC, respectively.